Virulence of entomopathogenic nematodes and their symbiotic bacteria against the hazelnut weevil Curculio nucum. (20th October 2015) - Batalla‐Carrera, L.; Morton, A.; Garcia‐del‐Pino, F.
Abstract: The virulence of different entomopathogenic nematode strains of the families Steinernematidae and Heterorhabditidae, isolates from Catalonia (NE Iberian Peninsula), and their symbiotic bacteria was assessed with regard to the larvae and adults of the hazelnut weevil, Curculio nucum L. (Coleoptera: Curculionidae). The nematode strains screened included one Steinernema affine, five Steinernema feltiae, one Steinernema carpocapsae, one Steinernema sp. (a new species not yet described) and one Heterorhabditis bacteriophora . The pathogenicity of all the strains of nematodes was tested on larvae and only four of them on adults of the hazelnut weevil. Larval mortality ranged from 10% with S. affine to 79% with Steinernema sp. Adult mortality was higher in S. carpocapsae, achieving 100% adult weevil mortality. The pathogenicity of the symbiotic bacteria Xenorhabdus bovienii, X. kozodoii, X. nematophila and Photorhabdus luminescens was studied in larvae and adults of C. nucum . In the larvae, X. kozodoii showed a LT50 of 22.7 h, and in the adults, it was 20.5 h. All nematodes species except S. affine tested against larvae showed great potential to control the insect, whereas S. carpocapsae was the most effective for controlling adults.